Fibroplasty (venoplasty) to facilitate transvenous lead placement: A single‐center experience. (20th July 2020) - Kella, Danesh K.; Isath, Ameesh; Yasin, Omar; Padmanabhan, Deepak; Webster, Tracy; Mulpuru, Siva; Cha, Yong‐Mei; Friedman, Paul A.
Abstract: Introduction: Venous stenosis is a well‐recognized complication of transvenous leads (TVLs) that is encountered during lead revisions or device upgrades. We here report the outcomes of TVL placement facilitated by fibroplasty or tunneling (TUN) procedure. Methods: We conducted a single‐center retrospective cohort study of all patients undergoing TVL implantation requiring fibroplasty or TUN from 2005 to 2017. Medical records and procedure reports were reviewed for relevant data. Outcomes for fibroplasty and TUN to facilitate TVL placement were compared. Results: Sixty patients had fibroplasty and thirty‐five patients had a TUN procedure. There was no difference in procedure success rates between the two groups (97% fibroplasty vs. 100% TUN; p = .98). The fluoroscopy time was longer (fibroplasty = 39.7 ± 21.5 min vs. TUN = 29.2 ± 21.3 min; p = .01) and the total procedural time was shorter in the fibroplasty group (fibroplasty = 247 ± 77.8 min vs. TUN = 287 ± 77.1 min; p = .01). TUN was associated with a significantly higher incidence of acute complications (fibroplasty = 0 vs. TUN = 8; p = .002) most requiring invasive intervention and/or transfusion with blood products. Long‐term complications requiring additional device‐related procedures were comparable between the two groups (fibroplasty = 6 vs. TUN = 6; logrank p = .21). Conclusions: For patients with venous stenosis requiring additional TVL, balloon fibroplasty is associated with similar rates of success and a significantly decreased incidence of acute complications when compared with subcutaneous TUN.